Correlation between MGMT methylation and the efficacy of bevacizumab in high-grade glioma - Yan, Chengrui; Bai, Xuexue; Wu, Chao; Ma, Wenbin; Feng, Ming (Frontiers in Oncology, 2025)
PurposeThe aim of this study is to investigate whether the therapeutic efficacy of bevacizumab (BEV) in the treatment of high-grade glioma (HGG) is associated with the methylation status of O6-methylguanine-DNA methyltransferase (MGMT) on the basis of excluding the interference from chemotherapy drugs.MethodsThis study included 57 patients with histologically confirmed HGG who, due to various reasons, were unable to complete the standard chemotherapy protocol and thus received BEV treatment. Patients enrolled in the study were divided into two groups based on their MGMT status: the unmethylated MGMT group and the methylated MGMT group. Depending on whether the numerical variables of the patients satisfied a normal distribution, either the T-test or the rank-sum test was employed. For the comparison of categorical variables, the chi-square test was used.ResultsAfter BEV treatment, both PFS and OS were higher in the methylated MGMT group compared to the unmethylated group. Additionally, the tumor control rate was also higher in the methylated group. Furthermore, in both patient groups, a decrease in steroid dosage was observed following BEV treatment, accompanied by an increase in KPS. Multivariate COX regression analysis revealed that radiotherapy and complete tumor resection were significant factors influencing PFS and OS in HGG patients. Additionally, pathological grade was found to influence PFS in HGG patients.ConclusionBased on the exclusion of the interference from chemotherapy drugs, our study is the first to confirm the correlation between the methylation status of MGMT and the therapeutic effect of BEV on HGG.